The creation of the Fundação Brasileira para a Conservação da Natureza - Juliana da Costa Gomes de Souza (História, Ciências, Saúde - Manguinhos, 2024)
This study within the field of environmental history explores the scenario amid which the Fundação Brasileira para a Conservação da Natureza (Brazilian Foundation for Nature Conservation) was founded between 1958 and 1966; this important Brazilian non-governmental organization headquartered in Rio de Janeiro worked at the local, national, and international levels. Primary documentary sources were utilized, along with research of the related literature. The conclusions demonstrate the importance of non-governmental organizations predating this foundation, and the influence of conservationists on its establishment and current work.